ChemInform Abstract: AVPO4F (A: Li, K): A 4 V Cathode Material for High‐Power Rechargeable Batteries. Issue 15 (24th March 2016) - Fedotov, Stanislav S.; Khasanova, Nellie R.; Samarin, Aleksandr Sh.; Drozhzhin, Oleg A.; Batuk, Dmitry; Karakulina, Olesia M.; Hadermann, Joke; Abakumov, Artem M.; Antipov, Evgeny V.
Abstract: Phase pure KVPO4 F is prepared by firing equimolar amounts of VPO4 and KHF2 under Ar (600 °C, 1 h).